Social Exclusion/Inclusion and Australian First Nations LGBTIQ+ Young People's Wellbeing - Soldatic, Karen; Briskman, Linda; Trewlynn, William; Leha, John; Spurway, Kim (Social Inclusion, 2022)
There is little known about the social, cultural and emotional wellbeing (SCEWB) of Aboriginal and Torres Strait Islander LGBTIQ+ young people in Australia. What research exists does not disaggregate young people’s experiences from those of their adult Aboriginal and Torres Strait Islander LGBTIQ+ peers. The research that forms the basis for this article is one of the first conducted in Australia on this topic. The article uses information from in-depth interviews to inform concepts of social inclusion and exclusion for this population group. The interviews demonstrate the different ways in which social inclusion/exclusion practices, patterns and process within First Nations communities and non-Indigenous LGBTIQ+ communities impact on the SCEWB of these young people. The research demonstrates the importance of acceptance and support from families in particular the centrality of mothers to young people feeling accepted, safe and able to successfully overcome challenges to SCEWB. Non-Indigenous urban LGBTIQ+ communities are at times seen as a “second family” for young people, however, structural racism within these communities is also seen as a problem for young people’s inclusion. This article contributes significant new evidence on the impact of inclusion/exclusion on the SCEWB of Australian First Nations LGBTIQ+ youth.